La ley y las prácticas de protección al consumidor en Perú - Roca, Santiago (2011)
This paper offers a panoramic evaluation of consumer protection in Peru up to the middle of 2010. It describes major consumer protection and related laws and analyzes some of its fundamental constraints in its implementation, basically: the imposition of the criteria of "diligent" consumer, the resistance to observe consumer protection norms related to general and abusive contractual clauses, impunity against junk and garbage goods and dangerous products, abandonment of protection of weights and measures in the market, lack of instruments and laboratories to analyze innocuousness of goods and services, passiveness in procedures and execution of resolutions in the informal sector, lack of sanctions for business exploitative conducts and abusive prices, and the predominance of intellectual property interests above those of the consumers. Surprisingly, the paper finds that there is not a clear mandate and institutional actuation regarding the rectorship authority in overall consumer protection matters but there exists relatively good determination in Lima for the resolution of individual consumer conflicts (this does not happen in most provinces or regions of the country given the lack of an effective decentralization scheme). Administrative justice authorities, however, have no hands to solve cases and procedures speedily and effectively bringing into the table the need for an urgent organizational and administrative restructuring. The paper finally finds that consumer associations play a positive role but need to be strengthened and that there is a need for the creation of a national consumer protection system that should articulate all institutions and actors under the leadership of a proactive consumer protection rectorship authority.